IMPROVING THE ABILITY OF MATHEMATIC STUDY PROBLEMS AND DISPOSITIONS SMP STUDENTS THROUGH IMPROVE METHOD - Rijaya Rijaya; Utari Sumarmo; Rudy Kurniawan ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2018)
This study aims to: 1) know the achievement of problem-solving abilities and mathematical disposition of students, 2) the interaction between the learning model and the level of students' abilities to the achievement of problem-solving abilities and mathematical dispositions and 3) the association of problem ability and mathematical disposition students. This research uses the quantitative approach with the experimental method. The instrument used is a type of description test. Data analysis was done quantitatively by using t-test and two-track ANOVA test. The result of this research concludes that the achievement of problem-solving ability and mathematical disposition of students who gain learning with method Improve is better than students who get conventional learning either reviewed based on the whole students and based on students' early math ability. There is no interaction between learning method factors and the level of students' early mathematical ability toward the achievement of mathematical problem-solving abilities. There is no interaction between the learning method and the students' early mathematical ability towards achieving mathematical disposition abilities. Students have a positive attitude towards the learning of mathematics and Improve Method.